2017
DOI: 10.1016/j.neuroscience.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of sestrin 2 potentiates the early onset of age-related sensory cell degeneration in the cochlea

Abstract: Sestrin 2 (SESN2) is a stress-inducible protein that protects tissues from oxidative stress and delays the aging process. However, its role in maintaining the functional and structural integrity of the cochlea is largely unknown. Here, we report the expression of SESN2 protein in the sensory epithelium, particularly in hair cells. Using C57BL/6J mice, a mouse model of age-related cochlear degeneration, we observed a significant age-related reduction in SESN2 expression in cochlear tissues that was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…This same innate capacity to adopt specific phenotypes also appears immanent in the macrophages of the cochlea, particularly those macrophages along the sensory epithelia. Prior studies of sensory epithelium macrophages indicate a site-dependent morphology for apical versus basal portions of the basilar membrane, suggesting a manifest immune capacity for cells of a dendritic shape versus amoeboid cells ( Yang et al , 2015 ; Frye et al , 2017 ; Zhang et al , 2017 ) mirroring that observed for microglia in the CNS ( Yin et al , 2017 ).…”
Section: Inflammatory Cells In the Cochleamentioning
confidence: 93%
See 2 more Smart Citations
“…This same innate capacity to adopt specific phenotypes also appears immanent in the macrophages of the cochlea, particularly those macrophages along the sensory epithelia. Prior studies of sensory epithelium macrophages indicate a site-dependent morphology for apical versus basal portions of the basilar membrane, suggesting a manifest immune capacity for cells of a dendritic shape versus amoeboid cells ( Yang et al , 2015 ; Frye et al , 2017 ; Zhang et al , 2017 ) mirroring that observed for microglia in the CNS ( Yin et al , 2017 ).…”
Section: Inflammatory Cells In the Cochleamentioning
confidence: 93%
“…Moreover, infiltrated mononuclear phagocytes, including immature and less differentiated macrophages and monocytes, have been reported in many cochlear anatomic sites subsequent to cochlear stress. In ears that have undergone acoustic trauma, these infiltrated cells have been reported as present in the spiral ligament adjacent to fibrocytes ( Hirose et al , 2005 ; Tornabene et al , 2006 ), in the scala vestibuli, modiolus, and lateral wall ( Sautter et al , 2006 ; Wakabayashi et al , 2010 ; Du et al , 2011 ), Reissner's membrane ( Sautter et al , 2006 ), and immediately beneath the basilar membrane in the scala tympani cavity ( Frye et al , 2017 ; Zhang et al , 2017 ; Dong et al , 2018 ; Frye et al , 2018 ; Hu et al , 2018 ).…”
Section: Inflammatory Cells In the Cochleamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, glutamine-dependent activation of mTORC1 is dependent on v-ATPase and also requires the adenosine diphosphate ribosylation factor 1 (ARF1) GTPase 119 . Although a number of studies show that alterations of these newly discovered mTOR regulators (for example, Sestrin2) may play a role in aging 120122 , their precise effects on life span and aging-related pathologies remain to be established.…”
Section: Tor As a Negative Regulator Of Life Spanmentioning
confidence: 99%
“…Mice deficient in all three sestrins exhibit reduced postnatal survival associated with defective mTORC1 inactivation in multiple organs during neonatal fasting, thus revealing a non-redundant mechanism by which the sestrin family of guanine nucleotide dissociation inhibitors (GDIs) regulates the nutrient-sensing Rag GTPases to control mTORC1 signaling [73]. Sestrin2 knockout mice displayed enhanced expression of proinflammatory genes and activation of basilar membrane macrophages; these results suggest that sestrin2 plays an important role in cochlear homeostasis and immune responses to stress [74]. Other phenotypes of sestrin2 knockout mice included worsened hair cell loss in gentamicin-treated cochlear explants, implying an important role of sestrin2 in protecting hair cells against gentamicin [75].…”
Section: Sestrins In Aging-related Clinical Conditions Other Than mentioning
confidence: 99%